Das Konzept der imitatio in Senecas 79. Luciliusbrief - Vogt-Spira, Gregor (Lucius Annaeus Seneca, 2021)
This article focuses on the literary notion of imitatio in two of Seneca’s Epistulae. Analysis of Ep. 79, a rather consequential text for this vexed philosophical and literary notion, demonstrates Seneca’s independence from the early imperial debate on both imitatio and aemulatio. In Ep. 84, Seneca reveals his basic stance, that the individual who manipulates previous models ought to be an imitator rerum, here situated within the framework of Stoic philosophy.